THE INFLUENCE OF LEARNING INSTRUMENTS PROBLEM BASED LEARNING MODEL TO IMPROVE PHYSICS LEARNING OUTCOMES IN STATIC FLUID - Pretti T. M. Ambarita; Sahyar .; Ridwan A.Sani (Jurnal Pendidikan Fisika, 2016)
The objective of this research were to produce a lesson plans and worksheets learning instrument design that corresponded to problem based learning models and analyze whether it was can improve student learning outcomes. This research development was done in classroom by using development research methods of Analysis Design Development Implementation and Evaluation (ADDIE). ADDIE method was used as a method for designing a lesson plans and worksheets that corresponded to it. Three stages of development of lesson plans and worksheets such as an assessment by a team of experts, small group, and a field test. Assessment by a team of experts based on theree aspects such as format, content, and language. In small group and field test based on a response of students sheet. The student response sheet contains of teacher's ability to teach. Worksheet assessment based on aspects of the format, content, and language. Assessment of student learning outcomes based on pretest and posttest were analyzed by ngain. The results of development of lesson plans and worksheets were validated by a team of experts on aspects of format, content, and language. The result both of development of lesson plans and worksheets in small group and field test produced good categories. There was an increased student learning outcomes of  first to third meeting with categories of low to moderate.